2015
DOI: 10.1161/circep.114.002394
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Ventricular Tachycardia Ablation in Patients With Continuous Flow Left Ventricular Assist Devices

Abstract: Background-Left ventricular assist devices (LVADs) are increasingly used as a bridge to cardiac transplantation or as destination therapy. Patients with LVADs are at high risk for ventricular arrhythmias. This study describes ventricular arrhythmia characteristics and ablation in patients implanted with a Heart Mate II device. Methods and Results-All patients with a Heart Mate II device who underwent ventricular arrhythmia catheter ablation at 9 tertiary centers were included. Thirty-four patients (30 male, ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
85
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(91 citation statements)
references
References 20 publications
5
85
0
1
Order By: Relevance
“…This may suggest that ablation should be considered after appropriate treatment of the underlying heart failure. In patients who develop arrhythmias following LVAD implantation, the authors hypothesize that the hemodynamic and electrophysiologic changes predispose these patients to an increase in event rate rather than overt worsening of the heart failure, consistent with prior studies . It should be noted that LVAD‐related events, including LV suction and atrial fibrillation, have a higher predisposition for VA likely not directly related to the underlying substrate.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…This may suggest that ablation should be considered after appropriate treatment of the underlying heart failure. In patients who develop arrhythmias following LVAD implantation, the authors hypothesize that the hemodynamic and electrophysiologic changes predispose these patients to an increase in event rate rather than overt worsening of the heart failure, consistent with prior studies . It should be noted that LVAD‐related events, including LV suction and atrial fibrillation, have a higher predisposition for VA likely not directly related to the underlying substrate.…”
Section: Discussionsupporting
confidence: 70%
“…showed that the prevalence of VA within 30 days of LVAD implantation was 20.2%, which did not improve after the first 30 days of implantation . The presence of VA confers a higher mortality rate, longer durations of hospitalization, and increased mortality . A study by Brenyo et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple mechanisms contribute but delayed incidence of VAs is mostly secondary to pre‐existing substrate combined with a lack of favorable remodeling from the LVADs 23, 24. Sustained VAs are well tolerated by the LVAD‐supported LV, but prolonged duration of VAs can result in right ventricular dysfunction and right heart failure, which can contribute to worse outcomes in LVAD patients 25, 26.…”
Section: Discussionmentioning
confidence: 99%
“…In 2016, while this study was being conducted, Sapp et al published the VANISH study which demonstrated the benefit of ablation over escalation of antiarrhythmic therapy in patients with ischemic cardiomyopathy (10). In addition, there has been some work examining the feasibility and utility of VT ablation in patients with VADs (11), but its role remains unclear.…”
Section: Discussionmentioning
confidence: 99%